2017
DOI: 10.1149/2.0661701jes
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Framework for Battery Cell Impact Safety Modeling Using LS-DYNA

Abstract: The development process of electrified vehicles can benefit significantly from computer-aided engineering tools that predict the multiphysics response of batteries during abusive events. A coupled structural, electrical, electrochemical, and thermal model framework has been developed within the commercially available LS-DYNA software. The finite element model leverages a three-dimensional mesh structure that fully resolves the unit cell components. The mechanical solver predicts the distributed stress and stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…Marcicki et al developed a coupled structural-electrochemical-thermal model in LS Dyna to simulate the response of pouch cells under spherical and cylindrical impact loading [68]. Tensile tests in different directions as well as compression tests were conducted on the separator and electrodes to determine their material properties and FE models were developed to validate the models.…”
Section: Pouched Cellsmentioning
confidence: 99%
“…Marcicki et al developed a coupled structural-electrochemical-thermal model in LS Dyna to simulate the response of pouch cells under spherical and cylindrical impact loading [68]. Tensile tests in different directions as well as compression tests were conducted on the separator and electrodes to determine their material properties and FE models were developed to validate the models.…”
Section: Pouched Cellsmentioning
confidence: 99%
“…In a review of mechanical modelling of lithium-ion batteries, Zhu identified aspects of mechanical behaviour inherent to lithium-ion cells that should be represented by accurate homogenized material models that included [10]: the pressure dependence of the compression stiffness of porous layers, the poromechanics of the electrolyte-filled porous structure of the jellyroll, anisotropy of individual layers, plasticity, and crack propagation. Despite the complexity of multi-physics in the jellyroll [11][12][13], a notable consensus has arisen within a growing body of research that structural properties can be adequately approximated in solid mechanical terms for the practical finite element simulation of lithium-ion cells [6,[14][15][16][17][18][19]. Due to the common motivation of simulating automotive crash events, research has been predominantly concerned with bending and compression deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Poisson's ratio [20] and has been likened to the behaviour of cellular materials [21]. To this purpose, crushable foam and honeycomb material models have been frequently employed for homogenization techniques in commercial finite element codes such as LS DYNA and Abaqus [4,15,18,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The stiffness of polymeric foams is strain-rate dependent and is generally characterized by three phases of compression [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Marcicki and Zhu 18 used a combination of material testing and finite element simulation of components to study the thermal runaway phenomenon of a power battery during a sudden external short circuit. The finite element model could predict the distributed thermal response of the battery in an external short circuit.…”
Section: Introductionmentioning
confidence: 99%